Answer:
There were 423 adult tickets sold.
Step-by-step explanation:
Let x = the number of adult tickets sold
Let x + 65 = the number of student tickets sold
x + x + 65 = 715
2x = 715
x = 357.5
x + 65 = 422.5 (round up)
Answer:
2c^2 - 2c - 3
Step-by-step explanation:
Next time, please share the answer choices. Thank you.
Group together the 'c' terms in 2 + 7c – 4c2 – 3c + 4:
2 + 4c and -4c^2 + 4 Then we have:
-4c^2 + 4c + 6
We should reduce this by factoring -2 out of all three terms:
2c^2 - 2c - 3 This is the desired quadratic in standard form.
Answer:
<h3>The length of y is 62.82 cm.</h3>
Step-by-step explanation:
We are given a right triangle with an angle 30°.
Opposite side of angle 30° is x and adjacent side is y.
Also, given length of side x=36.25 cm.
In order to find the value of y, we need to apply tangent trigonometrical ratio.
We know,
Therefore,
Plugging values of and x=36.25, we get
Plugging value of in above equation, we get
On multiplying both sides by y, we get
0.577y=36.25
Dividing both sides by 0.577, we get
y=62.82
<h3>Therefore, the length of y is 62.82 cm.</h3>
I've attached the complete question.
Answer:
Only participant 1 is not cheating while the rest are cheating.
Because only participant 1 has a z-score that falls within the 95% confidence interval.
Step-by-step explanation:
We are given;
Mean; μ = 3.3
Standard deviation; s = 1
Participant 1: X = 4
Participant 2: X = 6
Participant 3: X = 7
Participant 4: X = 0
Z - score for participant 1:
z = (x - μ)/s
z = (4 - 3.3)/1
z = 0.7
Z-score for participant 2;
z = (6 - 3.3)/1
z = 2.7
Z-score for participant 3;
z = (7 - 3.3)/1
z = 3.7
Z-score for participant 4;
z = (0 - 3.3)/1
z = -3.3
Now from tables, the z-score value for confidence interval of 95% is between -1.96 and 1.96
Now, from all the participants z-score only participant 1 has a z-score that falls within the 95% confidence interval.
Thus, only participant 1 is not cheating while the rest are cheating.
Answer:
(-7,-15)
Step-by-step explanation:
We can substitute first y in the second y. Both equations are also functions. We can merge the equations.
Substitute x = -7 in any given equations. I will choose the second equation to substitute in.
<u>Answer</u><u> </u><u>Check</u>
Substitute both x and y in both equations.
The equation is true for (-7,-15).
The second equation is true for (-7,-15).
Therefore our answer is (-7,-15)